Towards a better testicular sperm extraction: novel sperm sorting technologies for non-motile sperm extracted by microdissection TESE - Mangum, Cathy L. (Transl Androl Urol, 2020)
Non-obstructive azoospermia (NOA) is the most severe form of male factor infertility. It is characterized by a lack of spermatogenesis in the seminiferous tubules. Microdissection testicular sperm extraction (microTESE) has significantly improved testicular sperm retrieval rates compared to conventional techniques for NOA. Following testicular biopsy, the sperm is usually non-motile and contained within seminiferous tubules requiring extensive laboratory processing to find individual sperm sufficient for artificial reproductive technologies (ART). Current techniques include mechanical and enzymatic processing which is time-consuming and often damaging to sperm. We review novel techniques that may help improve sperm retrieval rates after microTESE including microfluidics (dielectrophoretic cell sorting, spiral channel sorting, and pinched flow fractionation), fluorescence-activated cell sorting (FACS), and magnetic-activated cell sorting (MACS).